Analisis Faktor-Faktor Yang Memengaruhi Skeptisisme Profesional Auditor Internal Pada PTKIN Badan Layanan Umum - Cahyadi, Ady; Rikawati, R. (IAIN Kudus, 2019)
This study aims to examine competence, independence, experience, ethics, and religiosity to the professional skepticism of internal auditors. This research is causal-comparative research. The data used are primary data in the form of questionnaires conducted at tertiary institutions under the Ministry of Religion and with the status of Public Service Agency (BLU). Questionnaires are sent online to internal auditors. The population of this research is 55 universities. The Determination of the sample is done using the convenience sampling method. Samples obtained amounted to 16 universities. Data analysis tools for hypothesis testing are performed using multiple regression analysis. The results of the analysis can be concluded that experience and ethics have a significant positive effect on the professional skepticism of internal auditors, while competence, independence, and religiosity have no effect on the professional skepticism of internal auditors.